2022
DOI: 10.1093/sleep/zsac242
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic pedunculopontine tegmental neurons control wakefulness and locomotion via distinct axonal projections

Abstract: Study Objectives The pedunculopontine tegmental nucleus (PPT) is implicated in many brain functions, ranging from sleep/wake control and locomotion, to reward mechanisms and learning. The PPT contains cholinergic, GABAergic and glutamatergic neurons with extensive ascending and descending axonal projections. Glutamatergic PPT (PPT vGlut2) neurons are thought to promote wakefulness, but the mechanisms through which this occurs are unknown. In addition, some researchers propose that PPT vGlut2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
1
1
0
Order By: Relevance
“…Kroeger et al [ 13 ] found that selective activation of the PPTg glutamatergic neurons can induce longer behavioral arousal and cortical activation, while inhibition reduces arousal and increases non-REM sleep. This is consistent with a recent study by Kroeger et al, they found photoactivation of the PPTg glutamatergic neurons can wake mice from non-REM sleep, and photoactivation of distinct axonal projections can lead to differences in waking behavior [ 50 ]. Glutamatergic neurons in the PPTg neurons are composed of, in addition to neurons that are most active during waking (Wake active neurons), neurons that are active both during waking and REM sleep (Wake/REM active neurons) and those that are most active during REM sleep (REM active neurons) [ 37 ].…”
Section: The Role Of Various Neurons In Sleep–wake In the Pptgsupporting
confidence: 93%
See 1 more Smart Citation
“…Kroeger et al [ 13 ] found that selective activation of the PPTg glutamatergic neurons can induce longer behavioral arousal and cortical activation, while inhibition reduces arousal and increases non-REM sleep. This is consistent with a recent study by Kroeger et al, they found photoactivation of the PPTg glutamatergic neurons can wake mice from non-REM sleep, and photoactivation of distinct axonal projections can lead to differences in waking behavior [ 50 ]. Glutamatergic neurons in the PPTg neurons are composed of, in addition to neurons that are most active during waking (Wake active neurons), neurons that are active both during waking and REM sleep (Wake/REM active neurons) and those that are most active during REM sleep (REM active neurons) [ 37 ].…”
Section: The Role Of Various Neurons In Sleep–wake In the Pptgsupporting
confidence: 93%
“…However, the specific pathway by which glutamatergic neurons promote arousal is not clear. Kroeger et al found that the glutamatergic neurons of the PPTg projections to the SN may promote arousal, while projections to the BF and LH may promote higher arousal levels under dynamic conditions [ 50 ]. Some evidence showed that dopaminergic neurons (SNc) received glutamatergic neurons input directly from the PPTg neurons [ 52 , 53 ].…”
Section: The Role Of Various Neurons In Sleep–wake In the Pptgmentioning
confidence: 99%